2006
DOI: 10.1080/13607860600640962
|View full text |Cite
|
Sign up to set email alerts
|

Activity as a predictor of mental well-being among older adults

Abstract: This eight-year follow-up study examines the roles of physical and leisure activity as predictors of mental well-being among older adults born in 1904-1923. As part of the Evergreen project, 1224 (80%) persons aged 65-84 years were interviewed at baseline (1988), and 663 (90%) persons in the follow-up (1996). Mental well-being factors including depressive symptoms, anxiety, loneliness, self-rated mental vigour and meaning in life were constructed using factor analysis. The predictors of mental well-being inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(169 citation statements)
references
References 57 publications
8
158
0
3
Order By: Relevance
“…Older people in the Netherlands link activities to maintaining and improving health, accepting health decline, and adjusting one's activity and expectations to satisfactory QoL (Puts et al 2007). In a study of Finnish elders, being mobile and physically active enhanced leisure activity, as was the case with the lack of morbidity and being physically active (Lampinen et al 2006). Among German elders, work-related success and experience have also been found to predict intensity of voluntary social engagement such as hobby work (Bukov et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Older people in the Netherlands link activities to maintaining and improving health, accepting health decline, and adjusting one's activity and expectations to satisfactory QoL (Puts et al 2007). In a study of Finnish elders, being mobile and physically active enhanced leisure activity, as was the case with the lack of morbidity and being physically active (Lampinen et al 2006). Among German elders, work-related success and experience have also been found to predict intensity of voluntary social engagement such as hobby work (Bukov et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of lapse in Silver Sneakers attendance was 28%-55% (p<0.05) higher for depressed participants during months [15][16][17][18][19][20][21][22][23][24]. For nondepressed Silver Sneakers participants, attendance of at least 2 visits/week during Year 1 was significantly associated with lower risk of depression in Year 2 (OR=0.54; 95%CI= 0.37, 0.79; p=0.002); a similar but statistically nonsignificant association was observed for previously depressed participants (OR=0.51; 95%CI=0.26, 1.02; p=0.06).…”
mentioning
confidence: 89%
“…Research has shown positive effects of being engaged in occupation such as disease prevention (Law, Steinwender & Leclair, 1998) and good health (Häggblom-Kronlöf & Sonn, 2005;Lampinen, Heikkinen, Kauppinen, & Heikkinen, 2006). Increased participation in activities leads to perceived improvement in life conditions, especially among the elderly who are widowed, have functional impairments or little contact with their families (Silverstein & Parker, 2002).…”
Section: Association Of Occupational Therapists 2002) the Canadianmentioning
confidence: 99%